KUB Perancangan Sistem Administrasi Pada Kelompok Usaha Bersama Berbasis Web Menggunakan Framework AngularJS - Rahadian Aulia Firda (Teknik Informatika, 2018)
Batam City is a strategic city adjacent to Singapore which includes Riau Islands Province. Batam lost the small island where the islands are inhabited by the fishermen. Fisher fisheries search livelihoods catch 8.686 households consisting of fishing activities as many as 7608 households and fish farming activities as many as 1713 households. This condition is, of course, ideal to be used as a starting point to increase production and market products with high economic value. However, the current reality is the sector. To other sectors. Batam is relatively small and still dominated by other sectors. Some of the things that are happening is the result of recapitulation of catch and fisherman cultivation is less effective because it is still done manually where fisherman catch report via short message (SMS) to extension team. The extension team recaptures all reports from each KUB so it will be difficult and time consuming. Therefore, it is needed a system of administration of Business Group Bersama (KUB) web-based so that the catch of fish and fisherman cultivation recorded in computer and facilitate for offices of Marine, Agriculture and Fishery (KP2) Batam production in each KUB Batam.